Genetic mechanisms of Escherichia coli resistance to target inactivation. Genes governing purine metabolism in enterobacteria: an unexpected sequence found via complementation selection - Cherepenko, E.; Craig, S. (Биополимеры и клетка, 1997)
Using enierobacterial strains having block in 3 different genes required for GMP synthesis, 3 groups of inserts with different restriction patterns were expected. But the fragments cloned represented 5 such, groups. One consisted of Salmonella typhimurium DNA fragments with 2 SacI sites available. Sequencing revealed 100 % homology of the cloned insert to the N-tenn of Y protein of the hemC-hemD linkage group of E. coli chromosome (85 min locus). It is suggested that Y may represent the gpp gene, coding for guanosinepentaphosphatase. It was also shown that a Salmonella DNA fragment resulting from PCR amplification with 20-mer primers complementary to the N- and C-terms of the hpt gene of E. coli did not encode an hypoxanthine phosplioribosyltransferase (HPRTase)and some other gene complemented GMP synthesis block in tie novo and salvage pathways in E. coli cells.